Cabazitaxel versus Abiraterone or Enzalutamide in Metastatic Prostate Cancer - de Wit, Ronald; de Bono, Johann; Sternberg, Cora N; Fizazi, Karim; Tombal, Bertrand; Wülfing, Christian; Kramer, Gero; Eymard, Jean-Christophe; Bamias, Aristotelis; Carles, Joan; Iacovelli, Roberto; Melichar, Bohuslav; et al. (The New England journal of medicine, 2019)
BACKGROUND: The efficacy and safety of cabazitaxel, as compared with an androgen-signaling-targeted inhibitor (abiraterone or enzalutamide), in patients with metastatic castration-resistant prostate cancer who were previously treated with docetaxel and had progression within 12 months while receiving the alternative inhibitor (abiraterone or enzalutamide) are unclear. METHODS: We randomly assigned, in a 1:1 ratio, patients who had previously received docetaxel and an androgen-signaling-targeted inhibitor (abiraterone or enzalutamide) to receive cabazitaxel (at a dose of 25 mg per square meter of body-surface area intravenously every 3 weeks, plus prednisone daily and granulocyte colony-stimulating factor) or the other androgen-signaling-targeted inhibitor (either 1000 mg of abiraterone plus prednisone daily or 160 mg of enzalutamide daily). The primary end point was imaging-based progression-free survival. Secondary end points of survival, response, and safety were assessed. RESULTS: A total of 255 patients underwent randomization. After a median follow-up of 9.2 months, imaging-based progression or death was reported in 95 of 129 patients (73.6%) in the cabazitaxel group, as compared with 101 of 126 patients (80.2%) in the group that received an androgen-signaling-targeted inhibitor (hazard ratio, 0.54; 95% confidence interval [CI], 0.40 to 0.73; P<0.001). The median imaging-based progression-free survival was 8.0 months with cabazitaxel and 3.7 months with the androgen-signaling-targeted inhibitor. The median overall survival was 13.6 months with cabazitaxel and 11.0 months with the androgen-signaling-targeted inhibitor (hazard ratio for death, 0.64; 95% CI, 0.46 to 0.89; P = 0.008). The median progression-free survival was 4.4 months with cabazitaxel and 2.7 months with an androgen-signaling-targeted inhibitor (hazard ratio for progression or death, 0.52; 95% CI, 0.40 to 0.68; P<0.001), a prostate-specific antigen response occurred in 35.7% and 13.5% of the patients, respectively (P<0.001), and tumor response was noted in 36.5% and 11.5% (P = 0.004). Adverse events of grade 3 or higher occurred in 56.3% of patients receiving cabazitaxel and in 52.4% of those receiving an androgen-signaling-targeted inhibitor. No new safety signals were observed. CONCLUSIONS: Cabazitaxel significantly improved a number of clinical outcomes, as compared with the androgen-signaling-targeted inhibitor (abiraterone or enzalutamide), in patients with metastatic castration-resistant prostate cancer who had been previously treated with docetaxel and the alternative androgen-signaling-targeted agent (abiraterone or enzalutamide). (Funded by Sanofi; CARD ClinicalTrials.gov number, NCT02485691.).
Keywords: senioři; taxoidy; senioři nad 80 let; Benzamides; prednison; doba přežití bez progrese choroby; Prostatic Neoplasms, Castration-Resistant; antagonisté androgenů; Androstenes; Kaplan-Meier Estimate; Middle Aged; Taxoids; mužské pohlaví; nádory prostaty rezistentní na kastraci; Infusions, Intravenous; Phenylthiohydantoin; androsteny; Kaplanův-Meierův odhad; intravenózní infuze; benzamidy; fenylthiohydantoin; Aged, 80 and over; Humans; Prednisone; Progression-Free Survival; lidé středního věku; Antineoplastic Combined Chemotherapy Protocols; Androgen Antagonists; protokoly protinádorové kombinované chemoterapie; Aged; nitrily; lidé; Male; Nitriles